Strategi Penerimaan Peserta Didik Baru di SD Muhammadiyah Program Khusus Boyolali - Pramachintya, Destyana Ratih; Sutrisno, Budi (Jurnal VARIDIKA, 2015)
The purpose of this research to describe the preparation of the acceptance of the new students in SD Muhammadiyah Program Khusus Boyolali, described the process of the acceptance of the new students, efforts in maintaining the process of the the process of the acceptance of the new students. This study used a descriptive qualitative method with a case study. The data used in the study is primary and secondary data. The source of data:  infor- mants, events and activities led by the sources informants. The data collection techniques used in the study was interviews, observation and analysis of documents. The validity of the data used in the study was data triangulation. The data analysis used in the study was inter- active model. Based on the result of the research, can be concluded that: 1) the preparation of teaching and learning process consisted of: a) the committee arrangement of the accep- tance, b) the arrangement of work program, c) the preparation of administration documents d) the preparation of infrastructure. 2) The process consisted of: a) the determination of the implementation stage of the acceptance of new students: the retrieval of the registration form b) the implementation of observation test of  new students (spoken and written), c) the implementation of  interview test of parents from new students, d) the selection process and assessment of observation test, e) the announcement of the acceptance result of new students, f) the administration of pre-register activity. 3) The efforts done to maintain the acceptance process: a) doing the preparation of the acceptance of new students earlier, b) enhancing the quantity of students by doing the promotion, c) maintaining a good relation- ship with the society, d) fostering active communication and discussion with the foundation leader, e) improving of the quality of schools and the human resources.